Tertullian’s Ad Martyras – a Manifest of a Rebel - Ambrazas, Justinas (Literatūra, 2021)
This paper presents a translation of Tertullian’s Ad Martyras into Lithuanian language and a brief introduction, which contains a short survey of Tertullian’s life, his audience, i.e., Christians of Africa, selection and motivation of provided examples in Ad Martyras.